2022
DOI: 10.3390/biomedicines10102502
|View full text |Cite
|
Sign up to set email alerts
|

Is Restless Legs Syndrome De Facto Thyroid Disease?

Abstract: While a primary role in the pathogenesis of restless legs syndrome (RLS) has been attributed to dysfunction of the dopaminergic system and impaired iron metabolism (particularly in the central nervous system), it has been hypothesized that an imbalance between thyroid hormones and dopaminergic activity may be the starting point for all aspects of RLS. Although this hypothesis was proposed more than a decade ago, it has not yet been verified beyond doubt. The main aim of this study is to compare the prevalence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Another study reported that patients with thyroid disease were more likely to develop RLS [ 13 ]. Especially, the risk of RLS in patients with Hashimoto’s disease was 2.56 times higher than that in the control group [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study reported that patients with thyroid disease were more likely to develop RLS [ 13 ]. Especially, the risk of RLS in patients with Hashimoto’s disease was 2.56 times higher than that in the control group [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that patients with thyroid disease were more likely to develop RLS [ 13 ]. Especially, the risk of RLS in patients with Hashimoto’s disease was 2.56 times higher than that in the control group [ 13 ]. Additionally, the occurrence of RLS is notably more common in individuals with hypothyroidism compared to those without it, and the incidence of hypothyroidism is substantially greater in individuals who have RLS than in those who do not [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various comorbidities such as kidney disease, cardiovascular diseases, obstructive lung disease, diabetes mellitus, hypothyroidism, chronic liver disease, and neurological, rheumatological and respiratory disorders may accompany RLS [ 2 , 16 , 17 , 18 , 19 , 40 ]. In a cross-sectional study including 5324 subjects, high cholesterol and hypertension were associated with RLS [ 41 ].…”
Section: Discussionmentioning
confidence: 99%